Some Research Results on Molluscs (Peanut Worm, Earth Worm) in Type Soil Eco-system, Vietnam - Huy, Ba Le; Xuan , Hoan Nguyen; Tan, Phong Nguyen; Lam, Ha Van; Dac, Chung Ngo; Thi, My Huong Nguyen; Nguyen , Trinh Trong (Some Research Results on Molluscs (Peanut Worm, Earth Worm) in Type Soil Eco-system, Vietnam, 2023)
For the first time, Vietnam has identified mangrove forests with Peanut worm to soften the soil and make the flora grow well. In the Peanut worm, there are 17-18 types of irreplaceable amino acids that are used as "panacea" foods for children. Humans and earthworms were found in coffee hills in basalt red soil, making the soil better and increasing the amount of humus related to the physical and chemical properties of the soil.